Substituted pyrrolo[1,2-a][1,2,4]triazolo-(triazino-)[c]quinazolines - a promising class of lipoxygenase inhibitors - V. V. Stavytskyi; I. S. Nosulenko; O. O. Portna; V. M. Shvets; O. Yu. Voskoboynik; S. І. Kоvalenko (Zaporozhye State Medical University, 2020)
The modern strategy of potential biologically active molecules search ("drug-design") is based on several innovation approaches. The method of high thrоughрut biological screening and method of molecular modeling deserves the most attention among such approaches. Lipoxygenase (LOX) is one owf the most perspective biological target for the substituted pyrrolo[1,2-a][1,2,4]triazolo-(triazino-)[c]quinazolines. So, molecular docking towards LOX and enzyme activating activity was investigated. The aim: Directed search of potential inhibitors of lipoxygenases among the unknown pyrrolo[1,2-a][1,2,4]triazolo-(triazino-)[c]quinazolines with the use of molecular docking and in vitro high throughput screening. Materials and methods. The research of lipoxygenase activity has been conducted for a number of original pyrrolo[1,2-a][1,2,4]triazolo-(triazino-)[c]quinazolines. Standard software was used for molecular docking and "drug-like" criteria research. Sodium letinate was used as a substrate to study soybean LOX enzyme activating activity. Results. The results of molecular docking have shown, that substituted pyrrolo[1,2-a][1,2,4]triazolo[1,5-c]quinazolines reveal a strong affinity toward LOX. The main types of interactions with aminoacid residues of mentioned the enzyme were identified. The conducted researches showed, that the substituted pyrrolo[1,2-a][1,2,4]triazino[2,3-c]quinazolines had the highest soybean LOX inhibition activity. Compounds with a fluorine atom and a 2-thienyl moiety in the structure revealed the highest activity inhibiting lipoxygenase by 36.33 % and 39.83 % respectively. The increased lipophilicity of triazine derivatives promotes a higher ability to inhibit soybean LOX, whereas, for triazole derivatives, which have lower molecular weight, an inverse relation is observed. Conclusions. The research of the substituted pyrrolo[1,2-a][1,2,4]triazolo-(triazino-)[c]quinazolines inhibition ability of soybean LOX as one of the possible mechanisms of their activity is proved and conducted. It is shown, that their lipoxygenase activity depends on lipophilicity and is defined by the availability of donor-acceptor fragments in the molecule, that is capable to form hydrogen and other types of interaction. The specified results are strong arguments for their further study as promising anti-inflammatory agents.